Dispersione scolastica. Ascoltare i protagonisti per comprenderla e prevenirla - Batini, Federico (DiScuTerE Didattica fra Scuola, Territorio e Educazione - Open Access, 2016)
A fact-finding research conducted together with college students to listen to secondary school students, teachers and directors about the issue of school dispersion. Which are the motivations behind the school dispersion? What we can do to prevent it? What is its consistency? How many students have failed the exams? These are some of the questions on which the perception of the participants has been solicited, with a particular focus on the students' voice, received by other older students.